2010
DOI: 10.1074/jbc.m110.169102
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Saccharomyces cerevisiae Erf2 Reveals a Two-step Reaction Mechanism for Protein Palmitoylation by DHHC Enzymes*

Abstract: DHHC protein acyltransferases (PATs) catalyze the palmitoylation of eukaryotic proteins through an enzymatic mechanism that remains largely unexplored. In this study we have combined genetic and biochemical approaches to examine the molecular mechanism of palmitate transfer of the yeast Ras PAT, which is composed of Erf2 and Erf4. The palmitoylation reaction consists of two steps; they are autopalmitoylation of the enzyme to create a palmitoyl-Erf2 intermediate followed by the transfer of the palmitoyl moiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
162
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(170 citation statements)
references
References 31 publications
8
162
0
Order By: Relevance
“…Two genetic variants of zDHHC9, R148W, and P150S, fall within the (R/K)XR motif and are asso-ciated with the Marfanoid features and psychological disorders characteristic of syndromic XLIDs. In a recent study, we screened the DHHC CRD of yeast Erf2 and found that the RPPR motif is involved in the catalytic step after the initial formation of the Erf2-palmitoyl thioester bond intermediate (15). This observation suggests that the palmitoylation defect in the XLID alleles of zDHHC9 might alter the kinetics of the autopalmitoylation step of the PAT reaction.…”
Section: Xlid-linked Zdhhc9 Mutants (R148w and P150s)mentioning
confidence: 98%
See 4 more Smart Citations
“…Two genetic variants of zDHHC9, R148W, and P150S, fall within the (R/K)XR motif and are asso-ciated with the Marfanoid features and psychological disorders characteristic of syndromic XLIDs. In a recent study, we screened the DHHC CRD of yeast Erf2 and found that the RPPR motif is involved in the catalytic step after the initial formation of the Erf2-palmitoyl thioester bond intermediate (15). This observation suggests that the palmitoylation defect in the XLID alleles of zDHHC9 might alter the kinetics of the autopalmitoylation step of the PAT reaction.…”
Section: Xlid-linked Zdhhc9 Mutants (R148w and P150s)mentioning
confidence: 98%
“…The resulting extract was spun at 3000 ϫ g for 15 min to remove cellular debris and unbroken cells to yield a whole cell extract. Purification procedure of the zDHHC9-GCP16 enzyme complexes from the whole cell extract has been previously described for Erf2-Erf4 (15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations